2019
DOI: 10.1039/c8an02177e
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman spectroscopy of microorganisms: limitations and applicability on the single-cell level

Abstract: Detection and characterization of microorganisms is essential for both clinical diagnostics and environmental studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…Although the assignment of the observed spectral features to the components of the cell membrane has been widely used and is practicable, recent studies have also reported that small molecules, related to the metabolic activity of bacteria, might contribute to the bacterial SERS spectra. The molecules concerned are metabolites of the purine degradation pathway, such as AMP, adenine, guanine, hypoxanthine, xanthine, and uric acid, secreted in response to the starvation conditions or physiological stress induced during sample preparation and signal acquisition …”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Although the assignment of the observed spectral features to the components of the cell membrane has been widely used and is practicable, recent studies have also reported that small molecules, related to the metabolic activity of bacteria, might contribute to the bacterial SERS spectra. The molecules concerned are metabolites of the purine degradation pathway, such as AMP, adenine, guanine, hypoxanthine, xanthine, and uric acid, secreted in response to the starvation conditions or physiological stress induced during sample preparation and signal acquisition …”
Section: Resultsmentioning
confidence: 75%
“…As a conclusion, the main differences between the SERS spectra of the three bacterial strains were noticed at the major feature region between 600 and 750 cm −1 and between 900 and 1,200 cm −1 . Moreover, it must be noted that all the assignments mentioned, relative to small purine molecules or to the components of the cell membrane, such as carbohydrates, amino acids, lipids, and proteins, could be correct, and signals originating from those various substances are overlapping …”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations